Perception and Practices of Health Data Privacy Protection among Consumers: An Empirical Study in One of Indonesia's Major Cities - Joni Yusufa; Dede Hermawan; Pradita Wuri Safitri; Ananda Sujati; Yuyut Prayuti; Arman Lany (Publikasi Indonesia, 2024)
Online information exchange has become commonplace in today's digital era, especially in the health sector. However, this also raises concerns regarding personal data privacy, especially health data. This study analyses consumers' perceptions and practices of health data privacy protection. The empirical method is used in this research. The data collection techniques used were literature studies, direct observation, and interviews. After the data is obtained, it is analysed through the stages of reduction, presentation of data, and conclusion. The results showed that consumers in Jakarta have a high level of perception of the importance of health data privacy; consumers understand that health data is sensitive information that needs to be protected. The law regarding the protection of consumer health data privacy in Indonesia is Law No. 27 of 2022 concerning Personal Data Protection. Practices in carrying out the personal data protection function by officers involve providing information and consultation to those in control of personal data to ensure compliance with the Personal Data Protection Law, monitoring to ensure that the rules applied by those in control of individual data are by the provisions of the applicable requirements, providing advice regarding the impact of personal data protection as well as monitoring the performance of individual data controllers and coordinating and taking action on issues related to activities in processing personal data.